PENGARUH DETERMINASI PENYALURAN KREDIT TERHADAP PROFITABILITAS BANK UMUM TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Jemmy Firdaus; Fakhry Zamzam; Harsi Romli (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2021)
This research aims to determine the influence of credit distribution determinations of Spread of Interest Rate (SIR), Loan to Deposit Ratio (LDR) and Non Perfoming Loan (NPL) against the profitability of commercial banks. The focus of research is on the banking industry listed on the Indonesia Stock Exchange (IDX). The population used in this research is a public bank listed on the Indonesia Stock Exchange in 2010-2018. This study uses multiple regression analysis methods with data processing techniques using 8 eviews. The test results proved that: 1) The increase in SIR has no effect on the profitability of the national commercial Bank located in IDX period 2010-2018. ; 2) The increase of LDR negatively affects the profitability of the national commercial Bank located in IDX period 2010-2018; 3) The NPL increase affects the increase in profitability of the national commercial Bank located in the IDX period 2010-2018.